2013
DOI: 10.7314/apjcp.2013.14.7.4061
|View full text |Cite
|
Sign up to set email alerts
|

"Sandwich" Chemotherapy (CT) with Radiotherapy (RT) Improves Outcomes in Patients with Stage IE/IIEExtranodal Natural Killer (NK)/T-cell Lymphomas

Abstract: The extranodal natural killer/T-cell lymphoma (ENKTL) shows high local or systemic failure rates when radiotherapy (RT) is taken as the primary treatment, suggesting a role for chemotherapy (CT) added to RT for this disease. However, the appropriate mode of combined modality therapy (CMT) has not been fully defined. A total of one hundred and twenty-one patients with ENKTL receiving sandwich CT with RT were reviewed between January 2003 and August 2012. The primary endpoints were the response rate, progression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
8
2
Order By: Relevance
“…ECOG PS and response to whole treatment were identified as predictors of OS and PFS in this study. Several studies have found that tumor response to initial CT is associated with patient prognosis . In contrast, this study showed the response to initial CT was not predicted outcome, but achievement of CR at completion treatment was associated with better PFS and OS.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…ECOG PS and response to whole treatment were identified as predictors of OS and PFS in this study. Several studies have found that tumor response to initial CT is associated with patient prognosis . In contrast, this study showed the response to initial CT was not predicted outcome, but achievement of CR at completion treatment was associated with better PFS and OS.…”
Section: Discussioncontrasting
confidence: 87%
“…Asparaginase‐based or pegaspargase‐based regimens provided favorable outcomes in newly diagnosed and relapse/refractory ENKL, nasal type . Several phase II studies with asparaginase‐based or pegaspargase‐based regimens combined with early RT has been shown to be effective for the treatment of newly diagnosed stage I/II ENKL . However, the toxicity profiles of above regimen limited its wide range of clinical application, especially for early‐stage ENKL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal first-line therapy for ENKL is evolving. The 5-year survival rates of limited stage ENKL treated with radiotherapy alone or with combination chemotherapy are both below 50% (Li et al, 2006;Zhang et al, 2013;Binesh et al, 2014). The main treatment for late stage ENKL is chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Others have argued that both recent response rate and long-term survival rate of combined therapy are superior to those of radiotherapy (Lee et al, 2008;Zhang et al, 2013). To further clarify the proper treatment for these patients so as to achieve long-term remission rate and survival rate, we employed Cochrane systematic reviews to assess related randomized controlled trial (RCT) in China and provide reference for clinical application.…”
Section: Introductionmentioning
confidence: 99%